Comparing poultry manure and cow dung on Arachis hypogaea growth in savanna environment - AISHA ABDULLAHI MAHMUD; MAHMOUD DOGARA ABDULRAHMAN (Smujo International, 2025)
Abstract. Mahmud AA, Abdulrahman MD. 2025. Comparing poultry manure and cow dung on Arachis hypogaea growth in Savanna environment. Nusantara Bioscience 17: 21-29. The study investigated the effects of poultry manure and cow dung on the growth of Arachis hypogaea L. (groundnut) in a controlled experimental setup at the botanical garden of Department of Plant Science and Biotechnology, Federal University Dutsin-Ma, Katsina State, Nigeria. The experiment followed a Completely Randomized Block Design (CRBD) with two organic fertilizer as treatments; poultry manure cow dung, and a control sample with no fertilizer. Two groundnut seeds varieties; pure red and light tan mixed each separately with cow dung, and poultry manure, and were subjected to viability test before planting. Growth parameters, including the number of leaves and plant height, were measured monthly for five months. The data obtained were analyzed using SPSS statistical software version 21, and significant differences were identified with Duncan’s multiple range tests at a 5% probability level. Results indicated a significant impact of organic fertilizers on the growth parameters. The results revealed that cow dung promotes early growth while poultry manure contributes more to reproductive success and yield. The control group showed significantly lower leaf development, with an average of (43.4) leaves. The findings highlight the role of organic fertilizers in enhancing plant leaf production, as they provide essential nutrients that are often deficient in untreated soils. In terms of plant height, the light tan variety treated with cow dung achieved the greatest average height (16.53 cm), surpassing both the control (15.4 cm) and the pure red variety treated with poultry manure (13.45 cm). Overall, the study emphasizes the importance of using organic fertilizers like poultry manure and cow dung to improve groundnut growth, reduce dependence on synthetic fertilizers, and enhance soil health. These organic amendments are beneficial for sustainable agricultural practices, contributing to improved crop yield and environmental sustainability.